2000
DOI: 10.1063/1.1288383
|View full text |Cite
|
Sign up to set email alerts
|

Improved quantum mechanical study of the potential energy surface for the bithiophene molecule

Abstract: The potential energy surface (PES) for the 2,2′-bithiophene molecule was investigated using Hartree–Fock, correlated MP2, MP4(SDQ), CCSD, and density functional theory levels. Distinct basis sets ranging from double-zeta to triple-zeta quality, with polarization functions added on all atoms, were employed as well as the Dunning correlated consistent polarized valence double-zeta (cc-pVDZ) basis set. Single point configuration interaction CISD calculations were also performed using the cc-pVDZ basis set. Harmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 40 publications
4
32
0
Order By: Relevance
“…However, it has been shown convincingly that this is due not to problems with DFT but to basis set insufficiency at the MP2 level. 64,91,92 Inclusion of zero point vibrational corrections flattens the potential energy surfaces further. 64 Thus, geometries of pyrrole oligomers are quite flexible and planarization energies are small.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown convincingly that this is due not to problems with DFT but to basis set insufficiency at the MP2 level. 64,91,92 Inclusion of zero point vibrational corrections flattens the potential energy surfaces further. 64 Thus, geometries of pyrrole oligomers are quite flexible and planarization energies are small.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding energy barrier is only 0.01-0.04 eV. [23,24,[30][31][32][33] By contrast, in the lowest excited state, 2T has been found to be trans-planar with a deep, steep single minimum on the potential energy surface (PES) [23,24]. One should thus expect that if the 2T molecule assumed the planar conformation, the lowest vertical absorption energy would be considerably lower than the gas-phase value, whereas the adiabatic energy would be reduced only marginally.…”
Section: Experimental Evidencementioning
confidence: 99%
“…The following section is devoted to the description of our computational methods. Note that some of our calculations with moderately sized basis sets reproduce previously published data [5][6][7][8] and are included mainly for the readerÕs convenience, to facilitate comparison with the more accurate results. Afterwards, we shall illustrate our numerical results and discuss their dependence on the electron correlation method and on the quality of the basis set.…”
Section: Introductionmentioning
confidence: 97%
“…Eventually, they were unable to claim convergence of the MP2 potential with respect to the basis set. Finally, Duarte et al [8] studied the effects of several density functionals as well as CCSD (coupled-cluster with single and double excitations) and MP4(SDQ) (fourth-order Møller-Plesset, neglecting triple excitations). Interestingly, these authors observed a fair agreement between the MP4(SDQ)/cc-pVDZ and B3LYP/6-311G** curves, thus reducing the ÔconflictÕ between wavefunction-based and density-functional theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation